Stabilitas Zeolit HY Hidrofobik terhadap Uji Hot Liquid Water (HLW) - Susanti, Yuni; Variyana, Yeni (Talenta Publisher (Universitas Sumatera Utara), 2021)
Initially, zeolite catalysts cannot be used for reactions involving hot liquid water, so it is necessary to modify the zeolite to be stable under these conditions. The synthesis of HY and hydrophobic zeolites aimed to determine the stability of zeolite in hot liquid water (HLW). The stability of zeolite in HLW is related to zeolite hydrophobicity. In this study, the main raw materials for the synthesis of HY zeolite were sodium aluminate (NaAlO2) and Ludox HS-40 by calcining the product at 350 oC for 1 hour. Furthermore, increasing the hydrophobicity of HY zeolite was carried out by modifying the external zeolite surface using organosilanes (aminopropyltriethoxysilane). The stability of two zeolites in HLW was set at 200 oC. Zeolite analysis used physical test and Fourier Transform-Infra Red (FTIR) Spectrometer. The results of the zeolite distribution in two phases confirmed that HY zeolite was completely dispersed in the water phase, while the zeolite one was dispersed in the organic phase. Moreover, the IR spectra of HY zeolite showed that the wide peak detection at wave number 720 cm-1 for beginning to disappear. This means that the HLW condition could be damaged to the d6r unit. Another result was shown by hydrophobic zeolite spectra with a stable peak for 72 hours. This indicates that the hydrophobic zeolite has thermal stability in HLW so that it can be used in chemical reaction catalytic applications that use on phase.